Implementasi Aplikasi Quizizz Sebagai Media Pembelajaran Bahasa Inggris Siswa Kelas V SDN 4 Kuranji - Yuliandini, Audi; Rosidik, Izam; Wulandari, Nourma Pramestie (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
Technology plays a crucial role in enhancing students' interest and understanding, particularly at the elementary school level. Therefore, students from the Faculty of Teacher Training and Education at the University of Mataram, participating in the 8th cohort of the Kampus Mengajar program and placed at SDN 04 Kuranji, developed the